Habitat preference and dispersal of a sand associated beetle, Apalus bimaculatus - Ahlbäck, Lina (SLU/Dept. of Ecology, 2010)
Species that have a high degree of specialization and poor dispersal ability can be more prone to extinction than more generalist species and good dispersers. How these species traits affect the viability of populations is dependent on landscape factors,such as isolation and connectivity. Additionally, interactions between species (e.g. symbiosis), and how these interactions vary spatially and temporally can have a large impact on populations. When the range and habitat areas of a species continuously decrease, management strategies are often needed if the species shall be able to survive. Management strategies have been formulated for the beetle Apalus bimaculatus (L.). The species is classified as Near Threatened (NT) due to a continued degradation of the quality and area of the species’ habitat. The beetle has a complex life-history which includes parasitism on a solitary bee species,Colletes cunicularius (L.). Both species are dependent on disturbance requiring bare sand habitats, which vary both in time and space. The dispersal ecology of A. bimaculatus is poorly known. An increased understanding would be very beneficial to help explain the species abundance pattern and the effect of landscape factors. A number of 31 study sites were selected from a set of locations that had previously been surveyed for A. bimaculatus (2004, 2005 and 2006). The study sites were censused for A. bimaculatus, C. cunicularius, and other sand associated hymenopterans. Habitat quality of the sites were estimated using a number of abiotic (e.g. temperature, habitat area) and biotic(presence of food resources) measures. I found A. bimaculatus in 17 study sites. In less than a third (9) of the study sites C. cunicularius were present, while in more than half of the sites (18) other sand associated hymenopterans were seen. A. bimaculatus were more often found in sites with few shadowing trees and where sub-patches were large with fine- or medium-grained sand as dominating fractions. In sites where the species was found, the habitat area was often much larger than in the sites where it was not detected. This study suggests that management strategies for this species should consider: 1) that cutting down trees can be good for sites with low solar insolation, 2) to make sure that at least some sub-patches are dominated by fine to medium grained sand, 3) that when searching for areas which would be suitable to restore or translocate A. bimaculatus to, it can be successful to use several species of sand associated hymenopterans as indicators.